PENGARUH MINAT BELAJAR SISWA MTS DI KOTA CIMAHI TERHADAP PEMBELAJARAN MATEMATIKA - Amaliya Desi Rahayu; Euis Eti Rohaeti; Eka Senjayawati (Departement of Mathematics Education, 2019)
The purpose of this study was to determine the effect of student learning interest on mathematics learning. The research method used in this study was to use the survey method. The sample size was 30 students, the researchers conducted a statement of questionnaire regarding student learning interest with the number of statements 15 positive and negative questionnaire statements. Based on the results of the questionnaire data calculation, students are more likely to dislike learning mathematics and have the results of acquisition data with a percentage of 60%. The effect of the causes of students not liking mathematics is the learning time factor that is nearing the time of going home from school so that it influences the concentration of students' mathematics learning during class hours. But students have an interest in working on math questions given by the teacher with the results of as much as 42%.